Keputusan Masyarakat Pengguna Jasa Layanan Keuangan Agen Perbankan Pemerintah - Avianti, Widiya (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
A change in the number of transactions occurring at BRILink Rei Cell indicates that there are differences in consumers' decisions to use the service, which can be influenced by various factors, such as service quality and business location. This study uses a quantitative method, which consists of verifiable and descriptive types. This study involved 96 respondents, and the accidental sampling technique was used. The results show that, both partially and simultaneously, service quality and business location influence the decision to use BRILink Rei Cell services. This is indicated by a t-test significance value greater than 0.05 and a calculated F value greater than the table F value. The results show that improving service quality and business location can increase the choice of using services at BRILink Rei Cell. Therefore, BRILink Rei Cell is advised to consider improving both qualities so that more people will use their services.